How molecular pathology is changing and will change the therapeutics of patients with follicular cell-derived thyroid cancer. Issue 5 (15th January 2009) - Couto, J Pinto; Prazeres, H; Castro, P; Lima, J; Máximo, V; Soares, P; Sobrinho-Simões, M
Abstract : Well-differentiated thyroid carcinomas comprise two well-defined histological types: papillary and follicular (PTCs and FTCs, respectively). Despite being derived from the same cell (thyroid follicular cell), these two types of tumour accumulate distinct genetic abnormalities during progression. The molecular pathology of thyroid cancer is now better understood because of our ability to identify RET/PTC rearrangements and BRAF mutations in the aetiopathogenesis of the large majority of PTCs and the high prevalence of RAS mutations and PAX8/PPARγ rearrangements in follicular patterned carcinomas (FTCs and follicular variant of PTCs). This review summarises most of the molecular alterations currently used as targets for new biological treatments and looks at some of the changes that are already occurring or may occur in the treatment of patients with thyroid cancer. For simplicity, the review is divided up according to the major genetic alterations identified in well-differentiated thyroid carcinomas (RET/PTC rearrangements, BRAF mutations, RAS mutations and mitochondrial DNA deletions and mutations) and their respective treatments.